BS EN IEC 62841-2-3 AMD 1. Electric motor-operated hand-held tools, transportable tools and lawn and garden machinery. Safety. Part 2-3. Particular requirements for hand-held grinders, disc-type polishers and disc-type sanders (21st February 2022) - British Standards Institution,
No abstract available